Experiences of newly qualified midwives during their transition to practice: a systematic review of qualitative research - Shi, Jinjin; Li, Xuemei; Li, Yongqi; Liu, Ying; Li, Junying; Zhang, Rongli; Jiang, Hui (Frontiers in Medicine, 2023)
Objective To summarize and evaluate the experiences and expectations of newly qualified midwives (NQMs) during their transition from school to clinical practice. One of the main objectives was to provide references for the development of midwifery professional teaching and provide a basis for hospital administrators and instructors of midwifery to develop guidelines and strategies. Methods A systemic review of qualitative research using meta-aggregation was conducted. We collected studies from 12 databases between inception and February 2023. All qualitative studies published in English and Chinese that reported on the experiences of NQMs during their transition to practice were included. Two independent reviewers assessed the study quality and the credibility of study findings by using the JBI Qualitative Assessment and Review Instrument. The process of searching followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations. Results A total of 14 studies were included, and 84 findings were extracted. The results were grouped into 8 new categories and synthesized into 3 main themes: multi-dimensional challenges, physical and emotional responses, and demands and expectations. The included studies were identified to be of good quality and the results of the methodological quality appraisal were all B grade or higher. Conclusion The transition period is a critical career development for NQMs. However, they faced various stress during the period, which had a negative impact on their physical and mental health. Therefore, it’s important to deeply understand their challenges and needs. And effective management strategies should be implemented, such as in-depth cooperation between hospitals and schools, improvement of the clinical transition support system, enhancement of continuing education, and standardization of the management system. This may be beneficial to improve the quality of clinical midwifery and maintain the stability and sustainable development of the midwifery team.